2021
DOI: 10.1136/bmjopen-2021-049901
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to follow-up after an abnormal cervical cancer screening result and the role of male partners: a qualitative study

Abstract: IntroductionCervical cancer is the leading cause of cancer deaths among women in Malawi, but preventable through screening. Malawi primarily uses visual inspection with acetic acid (VIA) for screening, however, a follow-up for positive screening results remains a major barrier, in rural areas. We interviewed women who underwent a community-based screen-and-treat campaign that offered same-day treatment with thermocoagulation, a heat-based ablative procedure for VIA-positive lesions, to understand the barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Our study and numerous others from LMICs have highlighted these access issues. 5,7,8,10,13 In our study, the majority of participants pointed to lower transportation costs as a key reason for preferring self-administration of topical therapies over provider-administration in a health facility. This is further demonstrated by a qualitative study from Malawi where women with abnormal cervical cancer screening results cited lack of transportation and high associated costs as a major reason for not presenting for treatment.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our study and numerous others from LMICs have highlighted these access issues. 5,7,8,10,13 In our study, the majority of participants pointed to lower transportation costs as a key reason for preferring self-administration of topical therapies over provider-administration in a health facility. This is further demonstrated by a qualitative study from Malawi where women with abnormal cervical cancer screening results cited lack of transportation and high associated costs as a major reason for not presenting for treatment.…”
Section: Discussionmentioning
confidence: 62%
“…11 There are high rates of loss-to-follow-up due to cost and transportation challenges when women screened in rural areas are referred to central facilities for treatment, 12 as well as lack of adequate skilled healthcare providers to offer treatment. 8,10,13 In a retrospective review of the 2011-2020 Kenya cervical cancer program data, linkage to treatment following positive screening results was 25-40%, even though a structured surveillance system was in place. 9 This gap is consistently observed across multiple LMICs, 5,8,10,11,13 and contributes to the disproportionate burden of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Other research from LMICs has shown that male partners can complicate adherence to sexual abstinence restrictions. 26 , 44 Although self-reported adherence to recommendations was very high, responses may be subject to acquiescence bias. An additional consideration is that infection rates may be different in populations with high HIV prevalence, although existing research is limited and suggests similar patterns to non-HIV populations.…”
Section: Discussionmentioning
confidence: 99%
“…Male involvement and support are important factors for women to participate in screening programs and adhere to treatment and follow-up recommendations, as demonstrated in qualitative studies in Malawi and Kenya among women attending cervical cancer screening programs [24,25]. Women who did not adhere to the follow-up recommendations mentioned lack of financial and emotional support by their male partners and did not inform their male partners about their HPV-positive result.…”
Section: Plos Onementioning
confidence: 99%